Desenvolvimento de critérios explícitos adaptados à realidade brasileira para avaliação do uso de medicamentos potencialmente inapropriados para idosos - Motter, Fabiane Raquel (Universidade do Vale do Rio dos Sinos, 2018)
The use of potentially inappropriate medications (PIMs) for older patients is a public health problem because it can compromise the effectiveness or safety of pharmacotherapy and is responsible for high rates of morbidity and mortality in this age group. Brazilian studies that investigated PIMs show that the prevalence of PIM use ranges from 28.0% to 82.6%. However, these studies used PIM lists developed in other countries in North America and Europe. The first Brazilian consensus on PIMs was published in 2016. Limitations reported by the authors included that the PIM list was based on previous versions of Beers (2012) and STOPP (2008), therefore, it did not include the most up-to-date versions published in 2015, and did not incorporate therapeutic alternatives. The aim of the present study is to develop and validate explicit criteria for the evaluation of PIMs prescribed to older patients in Brazil and their respective therapeutic alternatives. The development of this project comprises of two steps: 1- Elaboration of the preliminary PIM list for older patients based on a systematic literature review; 2 - Validation of the preliminary PIM list with the consensus of experts using modified Delphi technique; The elaboration of the preliminary list of MPIs was based on a systematic review of PIM lists published between January 1991 and April 2017. A qualitative analysis of the PIM lists was performed with the objective of verifying their applicability to the Brazilian market. This way, three lists of PIMs were selected: Beers’ 2015, STOPP 2015, and European Union (7) PIM. Thus, we obtained 153 explicit criteria distributed across seven instruments: PIMs–Pain and Inflammation, PIMs–Cardiovascular System, PIMs–Endocrine System, PIMs–Genitourinary, PIMs–Respiratory System, and PIMs–Central Nervous System. The first two were already validated using the modified Delphi technique. The items for which the lower limit of the 95% confidence interval (CI) was greater than or equal to 4.0 were considered to have been validated. The consensus on PIMs–Pain and Inflammation was formed by two rounds. A group of nine experts reached consensus on 98 (63.2%) of the 155 items. A consensus was reached for 31/34 concerns regardless of diagnosis, 4/4 dose concerns, 4/4 concerns about the duration of treatment, 19/20 concerns about use under specific conditions, 12/23 special considerations of use, and 28/68 therapeutic alternatives. In the consensus on PIMs–Cardiovascular System, a group of seven experts reached consensus on 84 of the 257 questions. A consensus was reached for 20/25 concerns independent of diagnosis, 4/4 concerns regarding dose, 37/57 concerns regarding use under specific conditions, 20/105 special considerations of use and 3/66 therapeutic alternatives. Although the development and validation of PIM lists based on expert opinion is a long and complex process, the development of PIM list based on recent consensuses will expand the knowledge about the PIMs in Brazil. Thus, this research will improve the understanding of the magnitude of PIM use in this country, and may contribute to the development of more effective strategies and interventions to reduce drug-related problems among older Brazilian patients.
Keywords: Lista de medicamentos potencialmente inapropriados; Idoso; Efeitos colaterais e reações adversas relacionados a medicamentos; Prescrição inadequada; Potentially inappropriate medication list; Aged; Drug-related side effects and adverse reaction; Inappropriate prescribing; ACCNPQ::Ciências da Saúde::Saúde Coletiva